An Analysis Of Teachers’ Perceptions Of Speaking Fluency Activities: Planning And Classroom - Espol (2017)
The purpose of this study was to explore the perceptions that a group of efl teachers have regarding speaking fluency and to obtain insight as to whether or not these views were reflected in their classroom practices. There were a total of 17 participants for this study. there were 10 males and 7 females. The participants ranged in age from 25 to 50 years of age. All of them are full time teachers in the institution and all of them teach advanced levels which according to the cefr are actually a b1+ or intermediate level. This study was a qualitative study due to the nature of the research questions which were three: what do teachers define as speaking fluency, are there any differences between those definitions and what the teachers do in class, and to what extent are speaking fluency activities developed in class? in order to obtain the necessary data semi-structured interviews using open-ended questions were used, classroom.